Cetacean strandings in Puerto Rico and the Virgin Islands - A. Mignucci-Giannoni, Antonio; Pinto-Rodríguez, Benito; Velasco-Escudero, Mario; A Montoya-Ospina, Ruby; M. Jiménez-Marrero, Nilda; Rodriguez-Lopez , Marta A.; H. Williams, Ernest; K. Odell, Daniel (J. Cetacean Res. Manage., 1999)
An assessment of cetacean strandings was conducted in waters off Puerto Rico and the United States and British Virgin Islands to identify, document and analyse factors associated with reported mortality events. Nineteen species of cetaceans were reported stranded. The total number of events recorded between 1867 and 1995 was 129, comprising over 159 individuals. The bottlenose dolphin (Tursiops truncatus) was the species most commonly found stranded, followed by Cuvier’s beaked whale (Ziphius cavirostris), sperm whale (Physeter macrocephalus), Atlantic spotted dolphin (Stenellafrontalis) and short-finned pilot whale (Globicephala macrorhynchus). An increase in the number of strandings is evident over the past 20 years, averaging 63.l% per year. Between 1990 and 1995, the average number of cases per year increased from 2.1 to 8.2. The seasonal pattern of strandings was not found to be uniform, with a high number of strandings occurring in the winter and spring. The monthly temporal distribution showed an overall bimodal pattern, with the highest number of cases reported for February, May and September. The spatial distribution was not even, and differed between countries, within countries, and between taxonomic groups and species. Aside from undetermined causes of mortality, the ratio of natural causes in relation to human-related causes was of 1.2:1. Between 1990 and 1995, a reduction of the percentage of undetermined cause of deaths resulted from the establishment of a cooperative effort in studying mortality in an organised and systematic manner. The most common natural cause of death category was dependent calf. The most common human-related cause categories observed were entanglement and accidental captures, followed by animals being shot or speared. Evaluation and recommendations to improve the research conducted are formulated, including guidelines for the development of a strategic plan to obtain baseline data on the biology and life history of cetaceans to be applied to their conservation and management.